Development and Evaluation of a Lapatinib-Loaded Lipomer Formulation for Pulmonary Drug Delivery - Nigar Kadar Mujawar; Jameel Ahmed S. Mulla (Journal of Pharmaceutical Innovation, 2027)

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

Lithologic provenance modelling of the Jaban meta-conglomerate and wacke band of Champaner Group, Gujarat, western India: An implication through field studies to decode the multiple lithological assortments from source to sink - Fardin Mulla; A Preethiga; Aditya U Joshi; Sakshi V Samji; Parita Gorania; M A Limaye; S J Desai (Journal of Earth System Science, 2025)

Effect of fly-ash as filler material on mechanical and thermal properties of jute-wool-epoxy hybrid composite: prediction using artificial neural network model - Manjunatha T. S.; Shivayogi B. H.; Maruthi Prashanth B. H.; Sandeepkumar Gowda; Asif Iqbal Mulla; Girish Ariga; Divijesh Puninchathaya P; Srinivasa C. S (Journal of the Indian Academy of Wood Science, 2025)

Co-amorphous Approach for Enhancing Rilpivirine Oral Bioavailability using CYP3A4 Inhibitor as a Co-former - Ashwini R. Madgulkar; Mangesh R. Bhalekar; Maryam S. Mulla (AAPS PharmSciTech, 2025)

Effect of Concentration of TiO2 Nanoparticles on Thiadiazole Derivative and Their Molecular Docking Study - Shivaprasadagouda Patil; Mahanthesh M. Basanagouda; S. Christopher Jeyaseelan; Bi Bi Ayisha Mulla; Gangadhar V. Muddapur; Uday M. Muddapur; Ashok H. Sidarai (Journal of Fluorescence, 2024)

Effect of coastal hypoxia on bacterial diversity as elucidated through 16S rRNA amplicon sequencing - Vruti V. Naik; Samir R. Damare; Shruti S. Shah; Damodar M. Shenoy; Amara Begum Mulla (Frontiers in Marine Science, 2024)
The formation of oxygen-depleted zones in the bottom waters is one of the most widespread phenomena in coastal areas. Upwelling episodes along India’s west coast due to the southwest monsoon increase biological productivity, further lowering the dissolved oxygen in the upwelled waters, which intensifies annually between June and October. Here, we have determined the changes in the microbial community in response to the varying oxygen levels and other physicochemical parameters at the Candolim Time Series Station using high-throughput sequencing. Amplicon Sequence Variants across all the samples collected in different seasons were mostly affiliated to the phyla Proteobacteria, Actinobacteria, Bacteroidetes, Verrucomicrobia, Chloroflexi, Firmicutes and Planctomycetes, with the most dominant being Proteobacteria (21-41%). Statistical analysis revealed that microbial diversity differed significantly with changing DO, ammonia, nitrate and nitrite concentrations during different seasons. The microbial community shift due to seasonal hypoxia results in the differential biogeochemical cycling of essential nutrients, with certain years seeing redox conditions up to sulphate reduction while certain years seeing only nitrogen loss. Future global warming scenarios will serve as a big challenge for understanding the role of microbial diversity and its implications in the cycling of natural elements.

Intertwined impacts of urbanization and land cover change on urban climate and agriculture in Aurangabad city (MS), India using google earth engine platform - Chaitanya B. Pande; Kanak N. Moharir; Abhay M. Varade; Hazam Ghassan Abdo; S. Mulla; Zaher Mundher Yaseen (Journal of Cleaner Production, 2023)

Experimental and Theoretical Spectroscopic Investigation on Coumarin Based Derivatives for Non-Linear Optoelectronics Application - Bi Bi Ayisha Mulla; Aravind R. Nesaragi; Mussuvir Pasha K. M; Malatesh S. Pujar; Ravindra R. Kamble; Ashok H. Sidarai (Journal of Fluorescence, 2023)

The clinical utility of polygenic risk scores in genomic medicine practices: a systematic review - Judit Kumuthini; Brittany Zick; Angeliki Balasopoulou; Constantina Chalikiopoulou; Collet Dandara; Ghada El-Kamah; Laura Findley; Theodora Katsila; Rongling Li; Ebner Bon Maceda; Henrietta Monye; Gabriel Rada; et al. (Human Genetics, 2022)
Genomic medicine aims to improve health using the individual genomic data of people to inform care. While clinical utility of genomic medicine in many monogenic, Mendelian disorders is amply demonstrated, clinical utility is less evident in polygenic traits, e.g., coronary artery disease or breast cancer. Polygenic risk scores (PRS) are subsets of individual genotypes designed to capture heritability of common traits, and hence to allow the stratification of risk of the trait in a population. We systematically reviewed the PubMed database for unequivocal evidence of clinical utility of polygenic risk scores, using stringent inclusion and exclusion criteria. While we identified studies demonstrating clinical validity in conditions where medical intervention based on a PRS is likely to benefit patient outcome, we did not identify a single study demonstrating unequivocally such a benefit, i.e. clinical utility. We conclude that while the routine use of PRSs hold great promise, translational research is still needed before they should enter mainstream clinical practice.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Levels of polycyclic aromatic hydrocarbons in edible and fried vegetable oil: a health risk assessment study - Jin-Kui Ma; Ke Li; Xiang Li; Seham Elbadry; Amal A. Raslan; Yan Li; Zohair S. Mulla; Asmaa B. M. B. Tahoun; Waleed Rizk El-Ghareeb; Xiao-Chen Huang (Environmental Science and Pollution Research, 2021)

Levels of biogenic amines in cheese: correlation to microbial status, dietary intakes, and their health risk assessment - Jin-Kui Ma; Amal A. Raslan; Seham Elbadry; Waleed Rizk El-Ghareeb; Zohair S. Mulla; May Bin-Jumah; Mohamed M. Abdel-Daim; Wageh Sobhy Darwish (Environmental Science and Pollution Research, 2020)

Biochemical and enzyme inhibitory attributes of methanolic leaf extract of Datura inoxia Mill. - Zabin K. Bagewadi; Uday M. Muddapur; Savita S. Madiwal; Sikandar I. Mulla; Aejaz Khan (Environmental Sustainability, 2019)

Spatial variability of microzooplankton in the central Arabian Sea during spring intermonsoon - S. Sai Elangovan; Manguesh Gauns; Amara Begum Mulla; Ayaz Ahmed (Marine Ecology, 2018)
Spatial variability of microzooplankton (MZP; organisms in size 20–200 μm) along with total heterotrophic bacteria (THB) and picophytoplankton in the upper 120‐m water column of the central Arabian Sea (AS) was studied during the spring intermonsoon period (March 2015). Six stations divided into three regions (northern, southern, and central) were sampled along 68°E transect, between 9°N and 21°N. A total of 25 species of MZP were recorded corresponding to loricate ciliates (11 species), aloricate ciliates (two species), and heterotrophic dinoflagellates (12 species). Along the transect, MZP total abundance that varied between 5 and 9 × 10 3 org./m 3 was largely contributed by ciliates, especially loricate ciliates (30%–62%) followed by heterotrophic dinoflagellates (23%–26%). MZP counts were lower in the central region ( SD ± 0.4, 7–8 × 10 3 org./m 3 ) than in the northern and the southern regions ( SD ± 0.7, 8–9 × 10 3 org./m 3 ) of the Arabian Sea. Heterotrophic bacterial counts were higher in the northern (28–202 × 10 3 cells/ml) and southern (16–92 × 10 3 cells/ml) and lowest in the central (13–89 × 10 3 cells/ml) region. In contrast, picophytoplankton showed higher counts in central (3–54 × 10 3 cells/ml) and southern (4–113 × 10 3 cells/ml) regions and lowest in the north (1–45 × 10 3 cells/ml). Strong positive coupling of MZP–THB (0.05 > p > 0.01) than that of MZP–picophytoplankton density and MZP–chlorophyll a concentration suggests the spatial scale variability and functioning of microbial loop in the central Arabian Sea during the spring intermonsoon period.

Role of In Vitro Release Methods in Liposomal Formulation Development: Challenges and Regulatory Perspective - Deepak Solomon; Nilesh Gupta; Nihal S. Mulla; Snehal Shukla; Yadir A. Guerrero; Vivek Gupta (The AAPS Journal, 2017)

Epidemiological investigation of Middle East respiratory syndrome coronavirus in dromedary camel farms linked with human infection in Abu Dhabi Emirate, United Arab Emirates - Salama Al Muhairi; Farida Al Hosani; Yassir M. Eltahir; Mariam Al Mulla; Mohammed F. Yusof; Wissam S. Serhan; Farouq M. Hashem; Elsaeid A. Elsayed; Bahaaeldin A. Marzoug; Assem S. Abdelazim (Virus Genes, 2016)

Intestinal Targeting of Ganciclovir Release Employing a Novel HEC-PAA Blended Lyomatrix - Mostafa Mabrouk; Jameel A. S. Mulla; Pradeep Kumar; Dharmesh R. Chejara; Ravindra V. Badhe; Yahya E. Choonara; Lisa C. du Toit; Viness Pillay (AAPS PharmSciTech, 2016)

An Observational Study of Blood Concentrations and Kinetics of Methyl- and Propyl-Parabens in Neonates - H. Mulla; S. Yakkundi; J. McElnay; I. Lutsar; T. Metsvaht; H. Varendi; G. Nellis; A. Nunn; J. Duncan; H. Pandya; M. Turner (Pharmaceutical Research, 2015)

Synthesis of silver nanoparticle decorated carbon nanotubes and its antimicrobial activity against growth of bacteria - Adawiya J. Haider; M. R. Mohammed; Emad A. Jaffar Al-Mulla; Duha S. Ahmed (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

Synthesis and pharmacological evaluation of novel thienopyrimidine and triazolothienopyrimidine derivatives - Jameel Ahmed S. Mulla; Mohammed Iqbal A. Khazi; Shridhar I. Panchamukhi; Young-Dae Gong; Imtiyaz Ahmed M. Khazi (Medicinal Chemistry Research, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Acetochlor Persistence in Surface and Subsurface Soil Samples - Rubem S. Oliveira; William C. Koskinen; Carrie D. Graff; James L. Anderson; David J. Mulla; Edward A. Nater; Diego G. Alonso (Water, Air, & Soil Pollution, 2013)

Productivity of rainfed wheat as affected by climate change scenario in northeastern Punjab, India - Bharat Bhushan Vashisht; D. J. Mulla; S. K. Jalota; Samanpreet Kaur; Harsimran Kaur; Sher Singh (Regional Environmental Change, 2013)

Biodegradation of 3-Nitrobenzoate by Bacillus flexus strain XJU-4 - Sikandar I. Mulla; T. P. Manjunatha; Robertcyril S. Hoskeri; Preeti N. Tallur; Harichandra Z. Ninnekar (World Journal of Microbiology and Biotechnology, 2011)

Biodegradation of 4-chlorobenzoic acid by Pseudomonas aeruginosa PA01 NC - Robertcyril S. Hoskeri; Sikandar I. Mulla; Yogesh S. Shouche; Harichandra Z. Ninnekar (Biodegradation, 2011)

Biodegradation of 2-Nitrotoluene by Micrococcus sp. strain SMN-1 - Sikandar I. Mulla; Robertcyril S. Hoskeri; Yogesh S. Shouche; Harichandra Z. Ninnekar (Biodegradation, 2011)

Farm Nutrient Management Practices in Two Geographically Diverse Watersheds in the Cottonwood River Watershed of Minnesota, USA - J. S. Strock; D. Bruening; J. D. Apland; D.J. Mulla (Water, Air, & Soil Pollution, 2005)

The human cytomegalovirus immediate early enhancer-promoter is responsive to activation by the adenovirus-5 13S E1A gene - D. M. Olive; W. Al-Mulla; M. Simsek; S. Zarban; W. Al-Nakib (Archives of Virology, 1990)

Impact of the insect growth regulator diflubenzuron on invertebrates in a residential-recreational lake - Arshad Ali; Mir S. Mulla (Archives of Environmental Contamination and Toxicology, 1978)